PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN (Studi Pada Saham Perusahaan Sektor Manufaktur Yang Listed di Bursa Efek Indonesia Periode Tahun 2009 â 2011) - 11.42.02.0048, Nandang Rochmat Susila (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examined the effect of investment decision, funding decision and structure of ownership on the firm value (study at Manufacturing Companies Listing in Indonesian Stock Exchange since 2009 until 2011 period). The sample in this study is a manufacturing company listed in Indonesian Stock Exchange (IDX) in span of years 2009â2011. Study sample is as much as 133 companies with 102 observations. Analysis of data using multiple regression analysis to all hyphotesis.The results showed that the investment decision have a significant positive effect to firm value. Funding decision have a significant negative effect to firm value, and Structure of ownership have a significant positive effect to firm value. With Goodness of Fit Test showed that 77,6% investment decision, funding decision and structure of ownership given effect to firm value, while the rest equal to 22,4% influenced by others variable which do not check. Keyword: investment decision , funding decision, structure of ownership and firm value.